Highlights of the 2019 honors session at the International Students’ Conference in Siberian Federal University, Russia - Maria Tarasova (Journal of the European Honors Council)
In honors education, creating a community of talented and ambitious students is a goal of primary importance. Honors sessions at international conferences contribute to globalization of the honors community and offer opportunities for starting the dialogue between honors students of different universities and diverse academic fields. The current note provides insight into the discussion at the honors session organized by SibFU Honors College at the international students’ conference “Prospect Svobodny 2019” at the premises of Siberian Federal University in Krasnoyarsk, Russia. The author describes the results of the interdisciplinary research activities presented at the session by honors students from Texas Christian University, Western Michigan University, University of New Mexico, Lamar University, and Siberian Federal University. The note reveals how the honors students’ sessions become forums for reflecting on the value of learner agency and also for exploring the areas of prospective collaboration in interdisciplinary research for honors students worldwide.